2018
DOI: 10.3892/ol.2018.9506
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑128 targeting RPN2 inhibits cell proliferation and migration through the Akt‑p53‑cyclin pathway in colorectal cancer cells

Abstract: Colorectal cancer (CRC) is a malignancy with high metastatic rates. The mechanism of miR-128 on the regulation of Ribophorin-II (RPN2) in CRC cells was explored in the present study. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) or western blot analyses were conducted to detect miR-128 and RPN2 levels in tissues and cell lines. AmiR-128 overexpression model was constructed using miR-128 mimic transfection in HT29 CRC cells. Then, cell proliferation was detected using a Cell Counting Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In contrast, inhibition of RPN2 expression reduced glycosylation, thereby attenuating cancer malignancy in breast cancer cells [23]. In Colorectal cancer (CRC) cells, decreased levels of MMP-2, MMP-9 and metastasis-associated protein 1, and increased levels of epithelial-cadherin and tissue inhibitor of metalloproteinases 2, were revealed in RPN2-upregulated cells [41]. Previous studies have also demonstrated that MMP-9 expression was positively-correlative with the phosphorylation of STAT3 and NFkB p65 [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inhibition of RPN2 expression reduced glycosylation, thereby attenuating cancer malignancy in breast cancer cells [23]. In Colorectal cancer (CRC) cells, decreased levels of MMP-2, MMP-9 and metastasis-associated protein 1, and increased levels of epithelial-cadherin and tissue inhibitor of metalloproteinases 2, were revealed in RPN2-upregulated cells [41]. Previous studies have also demonstrated that MMP-9 expression was positively-correlative with the phosphorylation of STAT3 and NFkB p65 [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…RPN2 is also required for the N-glycosylation of the epidermal growth factor receptor (EGFR), aiding the cell surface expression of EGFR and downstream signaling [83]. Although the molecular mechanisms underlying the abnormal expression of RPN2 in various cancer cells are unknown, RPN2 has been shown to be a target gene of microRNA-128 in colorectal cancer cells [84]. It has been reported that the expression of this small non-coding RNA changes during postnatal development [85,86], raising the possibility that RPN2 expression is cell-context-dependent and regulated dynamically during development and oncogenesis.…”
Section: Association Of Rpn2 and Tusc3 With Tumor Progressionmentioning
confidence: 99%
“…In neuroblastoma cells, PRUNE2 interacts with the AKT pathway [48]. Activation of the AKT pathway stimulates osteogenic differentiation [49,50], and interestingly, we observed a differential association of PRUNE2 with DDX6 in the hASCs induced to osteogenesis for 24 h. In cancer cells, RPN2 was described as being involved in the regulation of proliferation and migration [51,52], and in human airway smooth muscle cells, the protein MVP was found to be involved in growth/survival signaling pathways [53]. The action of MVP in these pathways was related to its association with MYH9 [53], a protein we also identified in the DDX6 complexes in the hASCs.…”
Section: Discussionmentioning
confidence: 59%